Features of development of boil-off reciprocating compressors used in complexes for storage and transportation of liquid natural gas - A. V. Burakov; A. A. Kotlov; L. G. Kuznetsov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение", 2025)
This article discusses complexes for the transportation, storage and transportation of liquefied natural gas, where compressors for the utilization of boil-off gas play a key role. The authors describe main features of boil-off compressors, the required parameters of reciprocating steam gas compressors, the main problems of calculating compressors in various systems, design methods for reciprocating compressors that improve the reliability of steam gas compressors to improve efficiency of liquefied natural gas storage and transportation systems.